(x+7)(x+4)(x+10)

asked by guest
on Jan 29, 2025 at 11:50 am



You asked:

Evaluate the expression: (x+7)(x+4)(x+10)\left(x + 7\right) \left(x + 4\right) \left(x + 10\right)

MathBot Answer:

Evaluated



(x+7)(x+4)(x+10)=(x+4)(x+7)(x+10)\displaystyle \left(x + 7\right) \left(x + 4\right) \left(x + 10\right) = \left(x + 4\right) \left(x + 7\right) \left(x + 10\right)


Expanded

(x+7)(x+4)(x+10)=x3+21x2+138x+280\left(x + 7\right) \left(x + 4\right) \left(x + 10\right) = x^{3} + 21 x^{2} + 138 x + 280